Nanopackaging Nanotechnologies and Electronics Packaging (Springer International Publishing, 2018)
This book presents a comprehensive overview of nanoscale electronics and systems packaging, and covers nanoscale structures, nanoelectronics packaging, applications of nanoparticles, graphene, carbon nanotubes and nanowires in packaging, and offers a roadmap for future trends. Composite materials are studied for high-k dielectrics, resistors and inductors, electrically conductive adhesives, conductive "inks," underfill fillers, and solder enhancement. Now in a second edition, Nanopackaging is an important reference for industrial and academic researchers, as well as practicing engineers seeking information about latest techniques. 12 new chapters address carbon nanotubes and nanowires, fabrication and properties of graphene, graphene for thermal cooling of microelectronics and for electrical interconnections, packaging of post-CMOS nanoelectronics, environmental and health effects of nanopackaging technologies, and more. This book is an ideal reference for researchers, practicing engineers, and graduate students who are either entering the field for the first time, or are already conducting research and want to expand their knowledge in the field of nanopackaging.